Fabricação e caracterização de cerâmicas com propriedades multifuncionais à base de CaCu3Ti4O12 modificadas com magnésio - Lourenço, Carolina [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
This work had as proposal a new stoichiometric system to be applied as varistor and dielectric, that is, the non - ohmic and dielectric properties were evaluated. A gradual replacement of the calcium element by magnesium was performed following the ratio: Ca1-xMgxCu3Ti4O12, in which x = 0.00; 0.05; 0.10; 0.50; 0.90 and 1.00. In addition to the proportion of magnesium, the influence of different sintering temperatures was also evaluated: 1000 °C, 1050 °C and 1100 °C, obtained from the study of the Dilatometry of the powders. The ceramics were prepared by reaction in the solid state and sintered in a chamber oven. In order to know the microstructure and the phases present in the new system, X-ray diffractometry (XRD) and scanning electron microstructure (SEM) techniques were used in both powders and disc-shaped pellets. Density and porosity, important parameters to keep the ceramic application viable, were studied through the Archimedes method and also by the gas pycnometry technique. In order to evaluate the properties of the pellets, direct current (DC) measurements were performed to study the varistor property of the compound by determining the following parameters from the E vs. J curves: nonlinearity coefficient (α), field electric rupture (Er) and leakage current (if), among others. Through the impedance / admittance spectroscopy technique (alternating current - AC), dielectric loss and permissivity were determined. Dense bulbs (average of 4.65 g/cm³) and excellent dielectric constant ε ~ 105 (when X = 0.10 sintered at 1050 °C were found, in addition to constant dielectric loss over a wide frequency range. Regarding the non-ohmic property, it was verified that only some compositions were able to demonstrate the defined behavior, with a limitation of the equipment. For those that demonstrated, it was possible to ... (Complete abstract click electronic access below)

Este trabalho teve como proposta um novo sistema estequiométrico para ser aplicado como varistor e dielétrico, ou seja, foram avaliadas a propriedade não ôhmica e dielétrica. Foi realizada uma substituição gradativa do elemento cálcio, pelo magnésio, seguindo a proporção: Ca1-xMgxCu3Ti4O12, no qual x = 0,00; 0,05; 0,10; 0,50; 0,90 e 1,00. Além da proporção de magnésio, também foi avaliada a influência de diferentes temperaturas de sinterização: 1000°C, 1050 °C e 1100 °C, obtidas a partir do estudo da Dilatometria dos pós. As cerâmicas foram preparadas por reação em estado sólido e sinterizadas em forno do tipo câmara. A fim de conhecer a microestrutura e as fases presentes no novo sistema, foram usadas as técnicas de difratometria de raios X (DRX) e microestrutura eletrônica de varredura (MEV) tanto nos pós quanto nas pastilhas em forma de discos. A densidade e a porosidade, importantes parâmetros para manter viável a aplicação da cerâmica, foram estudados através do método de Arquimedes e também pela técnica de picnometria gasosa. A fim de avaliar as propriedades das pastilhas, foram realizadas medições em corrente contínua (DC) para estudar a propriedade varistora do composto, através da determinação dos seguintes parâmetros a partir das curvas E vs J: coeficiente de não-linearidade (α), campo elétrico de ruptura (Er) e corrente fuga (if), entre outros. Através da técnica de espectroscopia de impedância/admitância (corrente alternada - AC), determinou-se a perda dielétrica e permissividade. Foram encontrados bulks densos (média de 4,65 g/cm³) e com excelente constante dielétrica ε ~ 105 (quando X=0,10 sinterizado à 1050 °C), além da perda dielétrica constante em um amplo intervalo de frequência. Acerca da propriedade não ôhmica, foi verificado que somente algumas ... (Resumo completo, clicar endereço eletrônico abaixo)
Manufacture and characterization of ceramics with magnesium modified CaCu3Ti4O12 based multifunctional properties
Keywords: Ceramica (Tecnologia); Estequiometria; Varistores; Microscopia eletrônica de varredura